(untitled) (National Administration Journal, 2025)
In today’s competitive and dynamic environment, the training of marketing professionals is essential to meet the needs of the global market. The Universidad Estatal a Distancia (UNED), through the School of Administrative Sciences (ECA), has offered a flexible educational approach for the preparation of marketing professionals. However, a decline in enrollment in this specialty has been observed in recent years, along with an apparent lack of student motivation. This work analyzes the factors that influence motivation and the choice of the marketing emphasis within the Business Administration program at UNED. Enrollment data and the importance of motivation in distance education are reviewed, as well as market trends that demand highly trained professionals in this field. Finally, the challenges and opportunities faced by marketing education are discussed, aiming to strengthen academic and professional performance. This analysis seeks to serve as input for institutional decision-making that promotes the growth and quality of the educational offering in marketing. KEYWORDS: Marketing, distance education, student motivation, UNED, professional training.